Mercury's Interior Structure Constrained by Density and P‐Wave Velocity Measurements of Liquid Fe‐Si‐C Alloys. Issue 1 (13th January 2021) - Knibbe, J. S.; Rivoldini, A.; Luginbuhl, S. M.; Namur, O.; Charlier, B.; Mezouar, M.; Sifre, D.; Berndt, J.; Kono, Y.; Neuville, D. R.; van Westrenen, W.; Van Hoolst, T.
Abstract: Experimental measurements of density by X‐ray absorption and of P‐wave velocity by ultrasonic techniques of liquid Fe‐(<17 wt%) Si‐(<4.5 wt%) C alloys at pressures up to 5.8 GPa are presented. These data are used to construct an Fe‐Si‐C liquid mixing model and to characterize interior structure models of Mercury with liquid outer core composed of Fe‐Si‐C. The interior structure models are constrained by geodetic measurements of the planet, such as the obliquity and libration of Mercury. The results indicate that S and/or C with concentrations at the wt% level are likely required in Mercury's core to ensure the existence of an inner core with a radius (below ∼1, 200 km) that is consistent with reported dynamo simulations for Mercury's magnetic field. Interior structure models with more than 14 wt% Si in the core, estimated for Mercury by assuming an EH chondrite‐like bulk composition, are only feasible if the obliquity of Mercury is near the upper limit of observational uncertainties (2.12 arcmin) and the mantle is dense (3.43–3.68 g·cm −3 ). Interior structure models with the central obliquity value (2.04 arcmin) and less than 7.5 wt% Si in the core, consistent with estimates of Mercury's core composition from an assumed CB chondrite‐like bulk composition, are compatible with 3.15–3.35 g·cm −3 mantle densities and an inner core radius below 1, 200 km. Interior structure models with the obliquity of Mercury near the lower observational uncertainty limit (1.96 arcmin) have a low‐density mantle (2.88–3.03 g·cm −3 ), less than 4 wt% Si in the core, and an inner core radius larger than 1, 600 km. Plain Language Summary: Mercury's large core is critical for understanding Mercury's composition and magnetic field, which is driven by core convection. Inferring Mercury's core composition from gravitational and rotational parameters requires a relation between density and composition of plausible core materials at high pressures and temperatures. This study presents experimental data that constrain the relation between density and composition of liquid Fe‐Si‐C metal alloys at pressures up to 5.8 GPa and temperatures of about 2000 K. The experimental results are integrated in interior structure models of Mercury to examine the range of possible core compositions. We conclude that only limited concentrations of silicon, carbon, and sulfur can be present in Mercury's core. High Si core concentrations, consistent with an EH chondrite‐like bulk composition for Mercury, would require a high density of Mercury's mantle and a large inner core. The lower Si core concentrations expected from a CB chondrite‐like bulk composition for Mercury place less stringent requirements on the planet. Carbon and/or sulfur in the liquid outer core can induce compositional buoyancy that is relevant for the generation of magnetic field in Mercury's core. Key Points: We present density and P‐wave velocity measurements of Fe‐Si‐C liquid metal up to 5.8 GPa and 2000 K Interior structure models for Mercury are calculated and constrained by geodetic observations to examine consequences of various core compositions Implications of the results for Mercury's bulk composition, formation, and dynamo generation are discussed